Weakly nonlinear boundary-value problems for differential systems with pulse influence - Boichuk О. A.; Khrashchevskaya, R. F. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The coefficient sufficient conditions for the existence of solutions and the iteration algorithm of constructing these solutions are obtained for weakly nonlinear boundary-value problems for systems of ordinary differential equations with pulse influence in the general case in which the number of boundary conditions does not coincide with the order of the differential system. The equation is derived for generating amplitudes of these boundary-value problems. This equation determines the amplitude of a solution, which can be regarded as generating for the required solution, and gives necessary conditions for the existence of this solution.